Identifikasi Kandungan Senyawa Aktif Antibakteri Ekstrak Rimpang Kunyit (Curcuma Domestica Val) dalam Menghambat Pertumbuhan Bakteri Cutibacterium Acnes Penyebab Acne Vulgaris - Alissa Zahara Anggelika; Hendra Tarigan Sibero; Ratri Mauluti Larasati; Syazili Mustofa (Pusat Riset dan Inovasi Nasional, 2026)
Acne vulgaris is a skin disorder caused by Cutibacterium acnes infection, commonly treated with antibiotics; however, prolonged use can induce resistance. Turmeric rhizome (Curcuma domestica Val.) contains curcumin, essential oils, and sesquiterpenoids with potential antibacterial properties. This study aimed to determine the inhibitory effectiveness of turmeric rhizome extract against C. acnes growth in vitro. This laboratory experimental study employed a post-test only control group design using the well diffusion method. The extract was prepared with 96% ethanol and tested at concentrations of 25%, 50%, 75%, and 100%, using 1.2% clindamycin as the positive control and distilled water as the negative control. The mean inhibition zone diameters were 3.92 ± 1.13 mm, 5.14 ± 0.86 mm, 6.84 ± 1.07 mm, and 15.2 ± 0.71 mm, respectively, while the positive control produced 22.9 ± 1.23 mm and the negative control showed no inhibition. The Minimum Inhibitory Concentration (MIC) was observed at 75% and the Minimum Bactericidal Concentration (MBC) at 100%. The turmeric rhizome extract exhibited antibacterial activity against C. acnes and has potential as a natural topical agent for acne vulgaris treatment.